MODEL CONNECTED DALAM PEMBELAJARAN IPS BERKARAKTER - Ignatius Sulistyo; Darsono Darsono; Pujiati Pujiati (Jurnal Studi Sosial / Journal of Social Studies, 2014)
The purposes of this research were to produce the Connected Model in social studies that can be used as an alternative to improve the learning outcomes of students in junior high, connected model to analyze the effectiveness of testing in social studies. This research method uses Research and Development (RD). Results showed that connected model product development in social studies learning was developed by using the research design development adopted the steps from Dick and Carey instructional design model, and then tested with the results of the development steps by Borg and Gall development research, conducted through 6 stages, namely: making needs analysis, planning or product development, or expert review of the expert validation, product revision, the test is limited, and, so models and reporting. Connected Model in the IPS learning effectively used in teaching social studies.Tujuan Penelitian ini adalah menghasilkan Model Connected pada mata pelajaran IPS yang dapat dijadikan alternatif untuk meningkatkan hasil belajar peserta didik di SMP, menganalisis pengujian efektifitas Model Connected pada mata pelajaran IPS. Metode penelitian ini menggunakan Research and Development (RD). Hasil penelitian menunjukkan pengembangan produk model Connected dalam pembelajaran IPS dikembangkan menggunakan model rancangan penelitian pengembangan mengadopsi langkah-langkah Dick and Carey sebagai model desain pembelajaran, kemudian hasil pengembangan diuji cobakan dengan langkah-langkah penelitian pengembangan Borg and Gall, yang dilaksanakan melalui 6 tahap, yaitu: membuat analisis kebutuhan, perencanaan atau pengembangan produk,  validasi ahli atau reviu ahli,  revisi produk, uji terbatas, dan, model jadi dan pelaporan. Model Connected dalam pembelajaran IPS efektif digunakan dalam pembelajaran IPS.Kata kunci:  ips, model pembelajaran connected, pendidikan karakter